Çağdaş sanatta mekansal öğe olarak cam - Eryılmaz, Ayşe (My University, 2007)
ÇAĞDAŞ SANATTA MEKANSAL ÖĞE OLARAK CAM Mekansal öğe olarak camı tanımlayabilmek için, önce mekanı ve sonra da mekan öğesi olarak camın yerini belirlemek gereklidir. Mimari sözlüğe göre mekan, kişiyi bulunduğu çevreden ayıran ve içinde eylemlerini sürdürmesine elverişli olan boşluktur. Tanımlı boşlukların mekana dönüşebilmesi için bir işleve sahip olması gereklidir. Boşluk hayat bulmalıdır. En bilinen anlamda, barınma ve korunma işlevlerini karşılamalıdır. Mekan ve mekan gruplarının biraraya gelişi sırasında oluşan meydanlar, yollar ya da o yerleşmedeki kültürel gelişmeyi yansıtan mekansal oluşumlar da toplumsal mekanlar olarak kabul edilir. Tüm bu mekan grupları bireye hizmet etmektedir ve bireyin ve bireylerin oluşturduğu topluluğun kültürüne göre şekillenmektedir. Mimari mekan ve insan arasındaki karşılıklı ilişki, bir taraftan kişisel düzenlemeleri, diğer taraftan bu düzenlemeleri somut mimari elemanlara dönüştürme çabalarını kapsamaktadır. Mimarinin üç temel elemanı 20. yy. başlarına kadar malzeme, mekan ve ışıktı. Kübizmden sonra, malzemenin sadece bir kabuk olduğu, mekanın önem kazandığı ve hemen ardından ışığın geldiği genel olarak kabul edilir. Mekan ışıkla varolur. Dışarıdan mekana giren ışık, hem “dıştaki dünyayı” hem de “içteki” bütün boşluğu ve boşluğun sınırladığı yüzeylerin renk, doku ve anlamlarını tanımlar. Işık mekana geçirgenlik özelliğine sahip cam sayesinde hizmet eder. 5000 yıldır bilinen tarihiyle cam, Roma’lıların ilk plaka camı geliştirmesiyle, mekana fonksiyonel olarak katılan bir araç olmuştur. Roma imparatorluğu’nun zayıf düşüp ikiye ayrılmasıyla, cam üretimi Bizans’a kaymış ve “cam mozaik” formuyla mimari mekanda sanat nesnesi olarak varolmaya başlamıştır. İlerleyen süreçte, mekanda ışığı artırmak üzere duvarlar delindikçe, sanatçı bu yüzeyleri işleme arzusuyla yeni teknikler geliştirmiş ve bu gelişmeler vitray cam kullanımını artırmıştır. Sanayi devrimi sonrası geliştirilen önce demir, sonra çelik karkas stürüktür sistemleri ve geniş ebatlarda plaka camların üretilmesiyle binalar, modern mimari açısından adeta heykel gibi varlık bulmuşlardır. Cam, modern mimarlıkta 19. yy.’ın materyalist tavrından farklı olarak, yeni gücü simgeleyen artistik ve ekspresyonist bir tavırla ele alınmaya başlamıştır. Camın tarihsel süreç içinde salt malzemeden simgeselliğe uzanan yolculuğu, şeffaflığın durağanlıktan, kurgulanabilen deneyimsel bir niteliğe dönüşümünün tarihçesi de sayılabilir. Bu simgesel anlamları ile birlikte cam, mimarın elinde iç ve dış arasındaki sınırları buharlaştırarak, sosyal değişim ütopyasının mimariye yansıttığı ışıltılı görüntü olarak, sanatçının elinde ise, yüksek bir deneyimin, berraklığın, çağdaş sanat ortamına saydam yansımaları olarak varlık bulmuştur.

GLASS AS A SPATIAL ELEMENT IN MODERN ART In order to define glass as a spatial element, it is first necessary to identify the space itself, and then the particular location of the glass as a spatial element. According to its architectural dictionary definition, a space is an empty locality which separates an individual from his or her surroundings and is suitable for carrying out certain actions. For a defined void to become a space, it must have a particular function. The void must come alive. In other words, to put it in terms of its most common functions, it must become capable of providing shelter and protection. The town squares, the streets, and the spatial formations reflecting the cultural development of a particular settlement—all of which emerge as various spaces and groups of spaces come together—are considered social spaces. All of these groups of spaces serve the individual and are shaped according to the culture of the particular community, which is comprised of the individual and all individuals in it. The interrelationship between architectural space and human beings consists of both individual arrangements as well as efforts to transform those arrangements into concrete architectural elements. Up until the early 20th century, the three primary elements of architecture were materials, space, and light. Since Cubism, it has become widely accepted that materials are but a shell, that space is of greater importance than originally believed, and that immediately after space comes light. Space comes into existence with light. Light entering the space from outside defines both “the outside world” and the entire void “inside,” as well as the colors, texture, and meanings of the surfaces delineated by the void. And light is able to serve space thanks to glass and the permeable quality that it possesses. With a history going back 5,000 years, glass originally took on its functional role in conjunction with space when the Romans developed the first plates of glass. When the Roman Empire grew weak and was partitioned, the center of glass production shifted to Byzantium and glass began to be used in architectural spaces as an art object, in the form of “glass mosaics.” Later, as walls were punctured in an effort to increase the amount of light entering a particular space, artists developed new techniques in their desire to treat such surfaces artistically, and these developments resulted in an increase in the usage of stained glass. With the onset of the manufacture of plate glass in large sizes, and the first iron and then later steel skeleton structure systems, which were developed after the industrial revolution, each building became, from a modern architectural perspective, a veritable statue. Unlike the materialist approach to glass espoused in the 19th century, in modern architecture, glass began to be treated with an artistic and expressionist approach, symbolizing its new power. The history of glass, as it has progressed along its journey from pure material to the symbolic, could also be considered the history of its transformation from the stagnation of transparency to material shaped by experiment and imagination. Together with these symbolic meanings, in the hands of the architect glass has blurred the divisions between interior and exterior to emerge as a shining image reflecting in architecture the utopia of social change, while in the hands of the artist, it has emerged to become the transparent reflection of supreme experience and clarity in contemporary modern.
Keywords: Cam; Çağdaş Sanat